POTENTIAL FRUIT AND VEGETABLE PRODUCTION IN UZBEKISTAN AND THE ROLE OF CLUSTERS IN THEIR ACTIVITIES (Web of Teachers: Inderscience Research, 2024)
This article has extensively studied the potential fruit and vegetable production in Uzbekistan and the advantages of the cluster system in this area, features of the development of fruit and vegetable clusters in Uzbekistan, the main tasks set for their improvement.